Supratentorial non-RELA, ZFTA-fused ependymomas: a comprehensive phenotype genotype correlation highlighting the number of zinc fingers in ZFTA-NCOA1/2 fusions - Tauziède-Espariat, Arnault; Siegfried, Aurore; Nicaise, Yvan; Kergrohen, Thomas; Sievers, Philipp; Vasiljevic, Alexandre; Roux, Alexandre; Dezamis, Edouard; Benevello, Chiara; Machet, Marie-Christine; Michalak, Sophie; Puiseux, Chloe; et al. (Acta Neuropathologica Communications, 2021)
The cIMPACT-NOW Update 7 has replaced the WHO nosology of “ependymoma, RELA fusion positive” by “Supratentorial-ependymoma, C11orf95-fusion positive”. This modification reinforces the idea that supratentorial-ependymomas exhibiting fusion that implicates the C11orf95 (now called ZFTA) gene with or without the RELA gene, represent the same histomolecular entity. A hot off the press molecular study has identified distinct clusters of the DNA methylation class of ZFTA fusion-positive tumors. Interestingly, clusters 2 and 4 comprised tumors of different morphologies, with various ZFTA fusions without involvement of RELA. In this paper, we present a detailed series of thirteen cases of non-RELA ZFTA-fused supratentorial tumors with extensive clinical, radiological, histopathological, immunohistochemical, genetic and epigenetic (DNA methylation profiling) characterization. Contrary to the age of onset and MRI aspects similar to RELA fusion-positive EPN, we noted significant histopathological heterogeneity (pleomorphic xanthoastrocytoma-like, astroblastoma-like, ependymoma-like, and even sarcoma-like patterns) in this cohort. Immunophenotypically, these NFκB immunonegative tumors expressed GFAP variably, but EMA constantly and L1CAM frequently. Different gene partners were fused with ZFTA: NCOA1/2, MAML2 and for the first time MN1. These tumors had epigenetic homologies within the DNA methylation class of ependymomas-RELA and were classified as satellite clusters 2 and 4. Cluster 2 (n = 9) corresponded to tumors with classic ependymal histological features (n = 4) but also had astroblastic features (n = 5). Various types of ZFTA fusions were associated with cluster 2, but as in the original report, ZFTA:MAML2 fusion was frequent. Cluster 4 was enriched with sarcoma-like tumors. Moreover, we reported a novel anatomy of three ZFTA:NCOA1/2 fusions with only 1 ZFTA zinc finger domain in the putative fusion protein, whereas all previously reported non-RELA ZFTA fusions have 4 ZFTA zinc fingers. All three cases presented a sarcoma-like morphology. This genotype/phenotype association requires further studies for confirmation. Our series is the first to extensively characterize this new subset of supratentorial ZFTA-fused ependymomas and highlights the usefulness of ZFTA FISH analysis to confirm the existence of a rearrangement without RELA abnormality.
Gesehen am 09.11.2021